2014
DOI: 10.1007/s12264-014-1466-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of extrasynaptic GABAA receptors inhibits cyclothiazide-induced epileptiform activity in hippocampal CA1 neurons

Abstract: Extrasynaptic GABA(A) receptors (GABA(A)Rs)-mediated tonic inhibition is reported to involve in the pathogenesis of epilepsy. In this study, we used cyclothiazide (CTZ)-induced in vitro brain slice seizure model to explore the effect of selective activation of extrasynaptic GABA(A)Rs by 4,5,6,7-tetrahydroisoxazolo[5,4-c] pyridine-3-ol (THIP) on the CTZ-induced epileptiform activity in hippocampal neurons. Perfusion with CTZ dose-dependently induced multiple epileptiform peaks of evoked population spikes (PSs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Also, the anesthetic 4,5,6,7-tetrahydroisoxazolo(5,4-c)pyridin-3-ol (THIP, gaboxadol) agonizes the δ subunit. THIP can reduce spikes in vitro and in vivo [ 125 , 126 ]. In a clinical study with a small sample size, a trend toward seizure reduction was demonstrated [ 127 ].…”
Section: Toward Antiepileptic Drugs That Target Tonic Gaba Signalingmentioning
confidence: 99%
“…Also, the anesthetic 4,5,6,7-tetrahydroisoxazolo(5,4-c)pyridin-3-ol (THIP, gaboxadol) agonizes the δ subunit. THIP can reduce spikes in vitro and in vivo [ 125 , 126 ]. In a clinical study with a small sample size, a trend toward seizure reduction was demonstrated [ 127 ].…”
Section: Toward Antiepileptic Drugs That Target Tonic Gaba Signalingmentioning
confidence: 99%
“…Acute perfusion with 50 lmol/L resveratrol reduced the bicuculline-evoked epileptiform activity in the CA1 region. Similarly, Wan et al demonstrated that cyclothiazide-induced epileptiform activity in CA1 neurons is suppressed by the activation of extrasynaptic GABA A Rs [29]. Together, these results further suggest that the GABA A R plays a prominent role in seizure generation, and resveratrol inhibits the electrical activity of hippocampal pyramidal neurons by enhancing GABAergic synaptic inhibition.…”
Section: Discussionmentioning
confidence: 66%
“…CTZ not only blocks AMPA receptor desensitization, but also inhibits GABAA receptors [ 8 ], and GABAA receptors were involved in the CTZ induced epileptiform activities in hippocampal neurons [ 9 11 , 13 ]. In this study, we reported further that, at the chronic phase of the CTZ seizure rat, there was a significant reduction of the GAD and GAT containing neurons in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclothiazide (CTZ) not only blocks AMPA receptor desensitization, but also inhibits GABAA receptors [ 8 ], which leads to induction of epileptiform activities in hippocampal neurons in both in vitro and in vivo preparations [ 7 , 9 11 ]. CTZ has also been demonstrated to acutely induce seizure behavior and epileptic EEG in freely moving rats [ 12 ], which involves extrasynaptic GABAA receptor participation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%